Briket Dari Limbah Organik Wortel Sebagai Upaya Pengolahan Limbah Industri Desa Giripurno, Kecamatan Bumiaji - Erza Anggara Verbiawan; Erwan Adi Saputro (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Informatika Indonesia Surabaya, 2022)
Briquette is an alternative energy source which is a non-renewable fossil fuel substituent. In addition, briquettes are also one of the products of biomass fuel which are currently widely used as alternative fuels. Organic waste from vegetables is one of the potentials that can be developed into fuel in the form of biochar. Giripurno Village is a village with quite large agricultural products, but the processing of agricultural waste in the village is still not carried out optimally. One of the agricultural commodities in Giripurno Village is carrots where organic carrot waste has the potential to be processed into biochar or briquette fuel products. The purpose of this carrot waste treatment is so that the village community understands the potential of organic waste produced from agricultural products in Giripurno Village. The method used is by compiling a module for making carrot organic waste briquettes and conducting socialization and submitting the module to village representatives in order to increase the wider economic potential of the village. The results of carrot briquettes have a burning time resistance of 51.05 minutes with an ash content of 18.12%. Thus, carrot briquettes are one of the potentials to improve the village economy and can be used as one of the main commodities of Giripurno Village.